PENGARUH PERMAINAN HALANG RINTANG BOLA TERHADAP KEMAMPUAN MOTORIK KASAR ANAK USIA 4-5 TAHUN DI TK ISLAM AKRAMUNNAS PEKANBARU - Loviana, Nurtia; N, Zulkifli; Hukmi, Hukmi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This study aimed to find out the effect of the ball obstacle course to gross motor skills of children aged 4 – 5 years old at Akramunnas the Islamic kindergarten in Pekanbaru. This study utilizes experimental method by one group pre-test post-test design. The samples taken in this study were 15 children of early age. While data collection techniques used is the observation. The data analysis technique uses t-test by utilizing SPSS 21 software. The analysis results of the data processing before the given treatment through the obstacle ball course, the gross motor skills of the 4 -5 years old children at Akramunnas the Islamic kindergarten in Pekanbaru obtained a total value of 172 with an average value is 11.47 and the analysis results of the data processing after the given treatment through the obstacle ball course, the gross motor skills of the children aged 4 -5 years at Akramunnas the Islamic kindergarten in Pekanbaru obtained a total value of 299 with an average value is 19.93. Based on data analysis, it can be seen that t-calculate = 17,398> t-table = 2.145 to Sig. (2-tailed) = 0,000. Because of Sig <0,05 it can be concluded that there is a difference in gross motor skills before and after the obstacle ball course done. It can be interpreted that there is an effect of giving the obstacle ball course to gross motor skills of 4-5 years old children at Akramunnas the Islamic kindergarten in Pekanbaru signified as much 41,23%.Keyword: Gross motor skills, ball obstacle course